A case study of stakeholders' perceptions of the management implications of the discipline provisions of the 1996 Schools Act in a rural Eastern Cape high school - Luggya, Daniel (Rhodes University, Faculty of Education, Department of Education, 2005)
South Africa's education management system has undergone a long history of transformation from the promulgation of the Bantu Education Act of 1953 to the realisation of democracy, and in this context, the South Mrican Schools Act (SASA) of l996. Apartheid legislation and the new democratic legislation have had a profound impact on the education leadership and management of schools, in which authoritarian management practices have been replaced by democratic management practices. However, democratic management practices have not yet had a significant effect in the leadership and management of schools, especially in the schools of previously disadvantaged areas. This thesis seeks to examine perceptions held by education stakeholders in the light of the rights of students as stipulated in the discipline provisions of the Schools Act of 1996, in one of the rural high schools in the Northern Region of the Eastern Cape Province. One of the most important discipline provisions is the ban on corporal punishment in schools. My intention in carrying out this research was not to generalise my findings but to understand the experiences and perceptions of the stakeholders in this school regarding the discipline provisions of the SASA. The data suggest that authoritarian education practices, especially corporal punishment, are still a factor in the maintenance of student discipline in this rural school. Stakeholders still believe in the use of corporal punishment as the only way of maintaining discipline and an orderly environment for teaching and learning. Such beliefs, assumptions and values concerning the use of corporal punishment are held by the principal, teachers, students and parents and have not changed since 1996. Beliefs, assumptions and values on the exclusive use of power by the principal on issues of suspension and expulsion are still being held by the above stakeholders in the school. The vision of the SASA that schools become autonomous institutions with democratic leadership and management practices does not seem to be practical because of the centralisation of power in the hands of the Provincial Head of the Education Department. This centralisation of power denies the principal and other stakeholders of the school the power to decide on crucial matters like the expulsion of misbehaving students, because it is the provincial Head who decides on the seriousness of offences committed by misbehaving students and subsequent expulsions. Apart from the location of power in the Provincial Head of the Education Department, the stakeholders of this school are also powerless on expulsion of students, or any other form of punishment because of the implication of the "right" to education in the Bill of Rights in the Constitution of the Republic of South Africa. The education department has to devise programmes that change the beliefs and assumptions of stakeholders on corporal punishment and decision-making on expulsions and suspensions. Unfortunately corporal punishment persists because parents use it in the home and support its use in school. Programmes on alternatives to corporal punishment are required for the smooth implementation of the SASA.
Keywords: High school students -- Discipline -- South Africa -- Eastern Cape; Discipline of children -- South Africa -- Eastern Cape; School discipline -- South Africa -- Eastern Cape; Corporal punishment -- South Africa -- Eastern Cape; School management and organization -- South Africa -- Eastern Cape; School discipline -- Law and legislation -- South Africa